Mutational spectrum of COL1A1 and COL1A2 in Egyptian patients with autosomal dominant osteogenesis imperfecta with clinical severity score and genotype/phenotype correlation. Issue 1 (January 2015) - Aglan, Mona S.; Abdel-Hamid, Mohamed S.; Otaify, Ghada A.; Ismail, Somaia M.; Effat, Laila K.; Temtamy, Samia A.
Abstract : Introduction: Osteogenesis imperfecta (OI) is a heterogeneous genetic disorder characterized by fractures with minimal or absent trauma and low bone mass. The clinical features of OI range from perinatal lethality to severe skeletal deformities, mobility impairments and short stature to nearly asymptomatic individuals with a mild predisposition. OI is inherited in both autosomal dominant and recessive inheritance patterns. The large majority of OI cases follow a dominant pattern of inheritance or are sporadic and result from heterozygous mutations in COL1A1 or COL1A2, the genes that encode the proαl (I) and proα2 (I) chains of type I collagen, the major structural protein of bone. Numerous approaches for the classification of OI have been published, among which the Sillence classification is the most commonly used. A more quantitative clinical scoring system to assess the severity of the cases was applied to our patients. Patients and methods: Here we report on the clinical and mutational spectrum of COL1A1 and COL1A2 genes in 11 patients from four unrelated Egyptian families with autosomal dominant osteogenesis imperfecta. We attempted a genotype–phenotype correlation based on our study in comparison with previous reports. Results: Direct sequencing of COL1A1 and COL1A2 revealed four distinct pathogenic mutations in the COL1A1 gene (p.G26D, p.Q822*, p.R1026* and p.R882*). In contrast, no mutations were identified in COL1A2 . Mutations cosegregated with the phenotype in all families. Conclusion: Our results show no common or hotspot COL1A1 mutations; this might reflect genetic heterogeneity of the disease in Egyptian patients. There was no clear-cut genotype–phenotype correlation that needs to be investigated by the study of more affected families. To our knowledge this is the first study to report on the mutational spectrum of autosomal dominant osteogenesis imperfecta among Egyptians.